Cheaters must prosper: reconciling theoretical and empirical perspectives on cheating in mutualism. (21st September 2015) - Jones, Emily I.; Afkhami, Michelle E.; Akçay, Erol; Bronstein, Judith L.; Bshary, Redouan; Frederickson, Megan E.; Heath, Katy D.; Hoeksema, Jason D.; Ness, Joshua H.; Pankey, M. Sabrina; Porter, Stephanie S.; Sachs, Joel L.; et al.
Abstract Cheating is a focal concept in the study of mutualism, with the majority of researchers considering cheating to be both prevalent and highly damaging. However, current definitions of cheating do not reliably capture the evolutionary threat that has been a central motivation for the study of cheating. We describe the development of the cheating concept and distill a relative‐fitness‐based definition of cheating that encapsulates the evolutionary threat posed by cheating, i.e. that cheaters will spread and erode the benefits of mutualism. We then describe experiments required to conclude that cheating is occurring and to quantify fitness conflict more generally. Next, we discuss how our definition and methods can generate comparability and integration of theory and experiments, which are currently divided by their respective prioritisations of fitness consequences and traits. To evaluate the current empirical evidence for cheating, we review the literature on several of the best‐studied mutualisms. We find that although there are numerous observations of low‐quality partners, there is currently very little support from fitness data that any of these meet our criteria to be considered cheaters. Finally, we highlight future directions for research on conflict in mutualisms, including novel research avenues opened by a relative‐fitness‐based definition of cheating.